The relationship between organizational capabilities and organizational performance of Malaysian local authorities : a resource based perspective / Jamaliah Said - Said, Jamaliah (2010)
Prior research on the factors influencing organizational performance has largely been grounded on the industrial organization perspective and thus tended to emphasize external factors. In the light of the Resource-Based View (RBV), which has suggested that certain key internal factors of an organization may be a source of organizational sustainable competitive advantage, this thesis tries to examine how organizational capabilities may be used to enhance organizational competitive advantage, measured in terms of their ability to perform above average industry performance. The relationships between organizational capabilities and organizational performance were tested with data collected from a survey of 140 Information Technology Managers and Accountants of the Malaysian Local Authorities (LAs). Previous RBV studies have argued that entrepreneurship capabilities (EC), Information Technology (IT) capabilities, the learning orientation (LO) and the use of strategic information are among the highest order capabilities important for organizational success.